A systematic review of the effects of character strengths‐based intervention on the psychological well‐being of patients suffering from chronic illnesses. (7th April 2020) - Yan, Tingting; Chan, Carmen W. H.; Chow, Ka Ming; Zheng, Wei; Sun, Meng
Abstract: Aims: To identify and evaluate the available evidence on the effectiveness of character strengths‐based intervention on the psychological well‐being of patients with chronic illnesses. Design: A systematic review with meta‐analysis. Data sources: Six electronic databases, including PubMed, EMBASE, EBSCO (CINAHL ® and MEDLINE), Web of Science, and PsycINFO, were searched from inception to December 2018. Review methods: The quality appraisal of evidence and summary of studies were undertaken following Joanna Briggs Institute critical appraisal checklists and the standard guidelines of Preferred Reporting Items for Systematic Reviews and Meta‐Analyses statement. Meta‐analysis was conducted according to Cochrane methods using RevMan 5.1. Results: Clinical studies on the character strengths‐based intervention for patients with chronic illnesses are limited. Eight studies involving 692 patients were identified and critically appraised in this review. Meta‐analysis results for three comparable studies indicated that character strengths‐based intervention was effective in improving the self‐esteem of patients with chronic illnesses and it significantly enhanced their general self‐efficacy and reduced their depression. Conclusions: The findings support the effectiveness of character strengths‐based intervention on improving the psychological well‐being of patients with chronic illnesses. However, caution is needed in interpreting these results due to limited studies and heterogeneity across studies. Further research is needed to provide strong evidence on the applicability of the intervention in clinical practice. Impact: This rigorous review provided current evidence on using character strengths‐based intervention to improve the psychological well‐being of patients with chronic illnesses. Character strengths‐based intervention provides a creative approach for patients because it may help improve their well‐being, happiness, self‐esteem, and self‐efficacy, and reduce depression and mental symptoms. Studies in different groups of patients suffering from chronic illnesses are recommended in the future. The character strengths‐based intervention should be replicated in various inpatient facilities and include a larger and a more ethnically and socioeconomically diverse sample. Abstract : 目的: 通过对慢性病患者心理健康状况的调查, 确定并评价基于性格优势的介入治疗的效果。 设计: 采用荟萃分析进行系统综述。 数据来源: 搜索包括PubMed因特网生物医学信息检索系统、EMBASE荷兰医学文摘数据、EBSCO文献数据库(CINAHL®护理学数据库和MEDLINE联机医学文献分析和检索系统)、Web of Science科研数据库平台和PsycINFO心理学文摘数据库在内的6个电子数据库从开始到2018年12月的文章。 审查方法: 根据乔安娜布里格斯研究所严格评价检查表和系统综述和荟萃分析优先报告的条目的标准指南, 进行证据质量评估和研究总结。根据Cochrane系统评价采用RevMan 5.1进行荟萃分析。 结果: 对慢性病患者进行基于性格优势的介入治疗的临床研究有限。本综述对8个涉及692例患者的研究进行了鉴定和批判性评价。三项比较研究的荟萃分析结果表明, 基于性格优势的介入治疗能有效提高慢性病患者的自尊感, 显著增强患者的一般自我效能, 降低患者的抑郁情绪。 结论: 本研究的发现验证了基于性格优势的介入治疗对改善慢性病患者心理健康的有效性。不过, 由于研究的局限性和研究的异质性, 应当审慎地阐明这些结果。需要开展进一步的研究为介入治疗在临床实践中的适用性问题提供有力的证据。 影响: 这一严格的综述为使用基于性格优势的介入治疗以改善慢性病患者心理健康提供最新的证据。基于性格优势的介入治疗为患者提供了一种创造性的方法, 因为其可以帮助改善患者的健康、幸福感、自尊和自我效能, 减少抑郁及精神症状。今后建议对不同慢性病患者群体开展研究。应当在不同医院中复制这项基于性格优势的介入治疗, 同时纳入更大范围、更具种族和社会经济多样性的样本。